2020
DOI: 10.1136/archdischild-2020-319569
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological surveillance study of female genital mutilation in the UK

Abstract: ObjectivesDescribe cases of female genital mutilation (FGM) presenting to consultant paediatricians and sexual assault referral centres (SARCs), including demographics, medical symptoms, examination findings and outcome.DesignThe well-established epidemiological surveillance study performed through the British Paediatric Surveillance Unit included FGM on the monthly returns.SettingAll consultant paediatricians and relevant SARC leads across the UK and Ireland.PatientsUnder 16 years old with FGM.InterventionsDa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…The actual prevalence of FGM/C among communities of migrants remains unknown [12,13]. Recent studies conducted in the United Kingdom (UK) showed signi cantly less cases of FGM/C than expected among minors according to prevalence estimates [14,15]. Nevertheless, the total number of women and girls who have undergone FGM/C is expected to grow in high-income countries because of increasing migration from countries where FGM/C prevalence remains high [16].…”
Section: Introductionmentioning
confidence: 99%
“…The actual prevalence of FGM/C among communities of migrants remains unknown [12,13]. Recent studies conducted in the United Kingdom (UK) showed signi cantly less cases of FGM/C than expected among minors according to prevalence estimates [14,15]. Nevertheless, the total number of women and girls who have undergone FGM/C is expected to grow in high-income countries because of increasing migration from countries where FGM/C prevalence remains high [16].…”
Section: Introductionmentioning
confidence: 99%
“…As such, the number of women/girls recorded on the Dataset as experiencing FGC/M types 1, 2 or 3-often considered the more harmful forms-in the UK may be as few as one or two. Epidemiological surveillance studies of clinic populations which do not suffer from the same data limitations also indicate that the numbers of cases of FGC/M occurring in the UK among children are low, particularly type 3 which tends to dominate public and popular discussions of FGC/M [3,[23][24][25][26].…”
mentioning
confidence: 99%
“…It is heartening that the number of children presenting with female genital mutilation (FGM) in the UK is less than expected from the estimates. 1 This is against a decade of changes to legal frameworks, including introducing FGM Protection Orders (FGMPOs) to protect girls and women at risk, alongside educational efforts to increase public awareness by a range of stakeholders.…”
mentioning
confidence: 99%
“…It is possible that FGM is abandoned after migration to the UK 1 and that anti-FGM measures need to be proportionate to the empirical evidence of the risk of FGM in the UK. However, there remain widespread concerns connected to discrimination towards women and girls of which FGM is one facet.…”
mentioning
confidence: 99%
See 1 more Smart Citation